Penilaian kelayakan rencana penanaman modal. Sebuah proyek bermotif laba - BASALAMAH, Salim (Gadjah Mada University Press, 1994)
Penilaian kelayakan rencana penanaman modal. Sebuah studi proyek bermotif laba